Forró eletrônico: uma análise sobre a representação da figura feminina - Freire, Libny Silva (2012)
Understanding music as a social manifestation, able to represent the time and culture along with their uses and mores, we look at the female figure in the electronic forró genre. Through a reading of the two genres musical and feminine we seek to identify the discourses present in the compositions, which refer to the feminine with thematic and/or terms referring to women. The study focuses on the compositions between 2009 to 2010 which became hits, ie.: those which have attained the highest number of listeners to 96 FM in a program named Paradão 96, broadcasted daily in the city of Natal/RN. Grounded in such concepts as cultural industry, mass culture, folkcommunication and gender, we analyze the processes of meaning production as a result of using the female figure and more accurately, about the representation of women through the discourse of this specific genre. We have chose the descriptive research with a qualitative approach and Discourse Analysis as a technique to identify the terms that refer to women, reflecting on what would be the possible meanings found in these speeches. We point out that in our investigation the female figure turned into a sexual object, erotic and submissive, in their turn, attributes usually given to women, was not a predominant result in the speech of electronic forró gender. With a variant thematic some playful and others about the betrayal of women we have identified that, to the surprise of many, including ourselves, romantic love was the one who led the audience requests during our time frame and that the female figure has several facets within the studied genre